Leadership Styles and Their Impact on Organizational Performance: a Business Management Perspective - M. Guffar Harahap; Muhammad Hizbullah; Haidir Lubis (MultiTech Publisher, 2023)
This study aims to investigate the relationship between leadership style and organizational performance in the context of business management. The background of the problem identifies the need for an in-depth understanding of the impact of various leadership styles on operational efficiency, employee satisfaction levels, and overall organizational performance. This research involves an in-depth literature analysis to understand leadership-related theories and findings in a business context. Research methodology includes quantitative data collection through surveys and regression analysis to test the relationship between the variables under consideration. The research location is within the context of diverse business organizations, covering various industrial sectors. The use of instruments such as the Multifactor Leadership Questionnaire (MLQ) is used to measure leadership style, while organizational performance indicators are obtained from financial data and performance appraisals.The results showed that transformational leadership style was positively correlated with organizational performance, while transactional leadership style was associated with increased operational efficiency. Democratic leadership style is positively related to the level of employee satisfaction. Contextual factors, such as market dynamics and technological developments, moderate the relationship between leadership style and organizational performance. The conclusion of this study is that the selection of the right leadership style, which is appropriate to the context and characteristics of the organization, can have a positive impact on the achievement of organizational goals. Contingency factors, such as management support and commitment, as well as organizational structure and corporate culture, also play a key role in determining the successful implementation of a particular leadership style